Influence of display parameters on perceiving visually simulated ego-rotations - a systematic investigation - Schulte-Pelkum, J.; Riecke, B. E; Heyde, M. von der (Tübingen Perception Conference (TWK), 2003)
In Virtual Reality, subjects typically misperceive visually simulated turning angles. The literature on this topic reports inconclusive data. This may be partly due to the different display devices and field of views FOV in the studies. Our study aims to disentangle the specific influence of display devices, FOV, and screen curvature on the perceived turning angle for simulated ego-rotations. In Experiment 1, display devices (HMDs vs. curved projection screen) and FOV were manipulated. Subjects were seated in front of the screen and saw a star field of limited lifetime dots on a dark background. They were instructed to perform simulated ego-rotations between 45 and 225$^°$ and they used a joystick to control the simulated turns. In a within-subject design, performance was compared between a projection screen (FOV 86$^°$$×$64$^°$), a HMD (40$^°$$×$30$^°$), and blinders that reduced the FOV on the screen to 40$^°$$×$30$^°$. Generally, all target angles were undershot. We found gain factors of 0.74 for the projection screen, 0.71 for the blinders, and 0.56 for the HMD. The reduction of the FOV on the screen had no significant effect (p=0.407), whereas the difference between the HMD and blinders with the same FOV was highly significant (p<0.01). In Experiment 2, screen curvature was manipulated. Subjects performed the same task as in Experiment 1, either on a flat projection screen or on a curved screen (radius 2m, FOV 86$^°$$×$64$^°$ for both). Screen curvature had a significant effect (p<0.001): While subjects turned too far on the flat screen (gain 1.12), they didn't turn far enough on the curved screen (gain 0.84). Subjects' verbal reports indicate that rotational optic flow on the flat screen was misperceived as translational flow. We conclude the following: First, display devices seem to be more critical than FOV for ego-rotations, the projection screen being superior to the HMD. Second, screen curvature is an important parameter to be considered for ego-motion simulation.
Keywords: Riecke; Riecke_2003; bernhard-riecke; iSpaceWeb; markus-von-der-heyde; talkWithoutPaper